Mulheres que não sonharam: a precariedade da rêverie materna e o não sonhado entre as gerações - Costa, Victor de Jesus Santos (2021)
This work is a reflection about the mother-son relationship based on the clinical experience of psychosis. The objective of this work is to understand the reason why, in some mothers, an intense anguish arises when their psychotic child shows a greater psychic development. Upon investigating the maternal reverie in the mother-baby link, the following hypothesis was formulated: what was not dreamt by the previous generations can contribute to the psychical suffering of the present generation, demanding psychical work on the part of it. This research is theoretical-clinical and the method employed is the psychoanalytic method of case construction. The clinical cases of a mother and a daughter were used as research material, both of whom had a history of psychotic crises, and were attended by the same university health service